Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1007/bf01315608
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin and G-17 dose responses in duodenal ulcer and controls

Abstract: Gastric acid and pepsin secretion and serum gastrin concentrations were measured in nine patients with uncomplicated duodenal ulcer (DU) and 10 normal controls in the fasting state and in response to graded doses of bombesin, a tetradecapeptide gastrin releaser, and, for reference, synthetic gastrin G-17. Serum gastrin with bombesin stimulation was significantly greater in duodenal ulcer (maximum 467 pg/ml) than in controls (153 pg/ml), while in seven of the DU group tested gastrin levels after a meal were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…4 B). Therefore, our results indicate that parietal cells of DU patients and normal controls have identical responsiveness (sensitivity) to circulating human G-17, a conclusion recently reached by Hirschowitz et al (5).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…4 B). Therefore, our results indicate that parietal cells of DU patients and normal controls have identical responsiveness (sensitivity) to circulating human G-17, a conclusion recently reached by Hirschowitz et al (5).…”
Section: Discussionsupporting
confidence: 67%
“…Studies by Isenberg, Lam, and their associates have suggested that parietal cells ofpatients with duodenal ulcer (DU)' are more responsive to gastrin than parietal cells of normal subjects (2,3). This is controversial, however, since acid secretory responsiveness to exogenous gastrin was similar in DU patients and controls studied by Hirschowitz et al (4,5). In the present study, we compared acid secretory responsiveness to human gastrin heptadecapeptide (G-17) in DU patients and controls.…”
Section: Introductionmentioning
confidence: 91%
“…Bombesin-stimulated gastrin release is considerably greater in DU patients than in controls. 26 DU patients, also showed a different pattern of acid secretion in response to bombesin. Low doses produced similar acid secretion in DUs and controls.…”
Section: Somatostatin In Duodenal Ulcermentioning
confidence: 89%
“…Following on the elegant studies of bombesin-stimulated gastrin and acid secretion by Hirschowitz et al 33 , the group in Glasgow evaluated acid secretion stimulated by the human bombesin equivalent GRP. They showed that GRP-stimulated acid secretion was exaggerated in patients with duodenal ulcer compared with uninfected patients or those with H. pylori infection without duodenal ulcer disease.…”
Section: Secretionsmentioning
confidence: 99%